ANALYSIS VEGETATION AND MAPPING OF INVASIVE SPECIES DISTRIBUTION IN MOUNT MASIGIT KAREUMBI, SOUTH SUMEDANG - SADIDA (NIM : 11514020), ASHMA
Mount Masigit Kareumbi (MMK) is a conservation area that is managed to support conservation and sustainable use of biological resources. One of the main conservation problems in most conservation areas in Indonesia, including in MMK, is the presence of invasive species. This species typically has the ability to invade the new environment and suppress the growth of other species, including the local species. This study aims to identify three invasive species dominating MMK, to map the distribution of the three invasive species, and to determine variables with high contribution to the distribution of invasive species. Data on invasive species were collected through vegetation surveys using 5x5 meter and 2x2 meter plots, respectively for shrubs and herbaceous habitus. The risk of the presence of invasive species was mapped using Maximum Entropy (Maxent) software, with two kinds of input data, i.e. the presence points of invasive species and some environmental layers, which include land cover, slope, Bare Soil Index (BSI), distance from road and Normalized Difference Vegetation Index (NDVI). Vegetation analysis shows that the dominant invasive species for herbaceous habitus is Centotheca lappacea with INP value 57.38%, while shrubs habitus is dominated by Clidemia hirta (INP 65.02%) and Stachytarpheta jamaicensis (INP 21.61%). The success of Maxent modeling was evaluated by the Area Under ROC Curve (AUC) values, with an AUC of 0.97 for C. lappacea; 0.98 for C. hirta and 0.954 for S. jamaicensis. The AUC values indicate the high accuracy in estimating the potential presence of all three invasive species. Based on the Jackknife test, the most influential variable in mapping the potential presence of invasive species for the three species is temperature. This study hence provides essential information for managers in monitoring and dealing with invasive species problems in MMK.